Study of corrosion behaviour of zinc in potassium hydroxide electrolyte - Wan Marinah Izzati Wan Ismail (2017)
Two types of zinc (Zn) was immersed in different concentration of potassium hydroxide (KOH) aiming at the preparation of corrosion behaviour of Zn in KOH, which led by producing the hydrogen evolution gas. Zn that been used in this study were existing commercial Zn and 99.9% pure Zn. In this study, the characterization of Zn was studied, this is including hydrogen evolution gas, corrosion rate, morphology analysis and structural analysis. In this experiment, instruments that used are scanning electron microscopy (SEM) and X-ray diffraction (XRD). The volume of hydrogen evolution gas was increasing until it attain the maximum level concentration of KOH, 6 M. Meanwhile, both sample of Zn that soaked in 6 M KOH had the highest rate of corrosion with 9.95 mpy, respectively. From the SEM micrographs of sample showed that Zn have reacted and corrode when immersed in KOH. The analysis from XRD for both types of Zn showed that the immersion of KOH electrolyte into Zn gives some effect where the surface of Zn showed white patch. This is due to oxide presence at Zn surface.